(untitled) (Semiárida, 2018)
The rumen digestion of three maize hybrids with contrasting characteristics: flint (PROZEA 33), semi dent (AW 190 mg) and dent (CL 849 EXP), presented in the form of whole grains and three milling fractions, was evaluated. Each material was incubated in the rumens of 3 Hereford steers, fitted with rumen cannulaes, in nylon bags, for 3, 6, 9, 12, 24 and 48 hours for the three fractions, and 48 hours only for whole grain. The information obtained was fitted by an exponential equation with lag time, and the results subjected to analysis of variance and compared by test of Tukey. The highest effective degradability (ED) (p<0.05) was that of the dent hybrid, followed by the semi dent and, finally, the flint hybrid, but the last two were not significantly different. The comparison between fractions shows that the highest ED was found in the smallest one (p<0.05), with no differences between the other two. The ED of the whole grains was very low for all hybrids. It is concluded that the particle size obtained by grinding and the hybrid type affect the rumen digestion of the maize grain, and that the whole grains of maize are poorly digested.